Intraveous gammaglobulin in systemic lupus erythematosus - Badillo Tenorio Rocio Elizabeth; Rivas Larrauri Francisco Eduardo (Instituto Nacional de Pediatría, 2014)
Systemic lupus erythematosus (SLE) is a chronic autoinmune multisystemic disease. Intravenous immunoglobulins (IVIg) have been previously used for the treatment of primary immunodefi- ciency diseases. In addition IVIg is used for a few autoimmune diseases, such as immune thrombocytopenic purpura. IVIg is an immunomodulatory agent capable of modulating autoinmu- nity and also provide defense against infection, IVIg has been used successfully in SLE. We review the role of IVIg in SLE as a therapeutic option.